Estimation of genetic parameters for resistance to gastro-intestinal nematodes in pure blood Arabian horses. Issue 4 (March 2015) - Kornaś, Sławomir; Sallé, Guillaume; Skalska, Marta; David, Ingrid; Ricard, Anne; Cabaret, Jacques
Graphical abstract: Highlights: Eight percent of the observed variation for strongyle egg excretion has a genetic origin. Heritability increases with age from 0.04 in juveniles to 0.21 in adult horses. Similar genetic architecture was found for strongyle egg counts in juvenile and adult horses. Abstract: Equine internal parasites, mostly cyathostomins, affect both horse welfare and performance. The appearance of anthelmintic-resistant parasites creates a pressing need for optimising drenching schemes. This optimization may be achieved by identifying genetic markers associated with host susceptibility to infection and then to drench carriers of these markers. The aim of our study was to characterise the genetics of horse resistance to strongyle infection by estimating heritability of this trait in an Arabian pure blood population. A population of 789 Arabian pure blood horses from the Michałów stud farm, Poland were measured for strongyle egg excretion twice a year, over 8 years. Low repeatability values were found for faecal egg counts. Our analyses showed that less than 10% of the observed variation for strongyle faecal egg counts in this population had a genetic origin. However, additional analyses highlighted an age-dependent increase in heritability which was 0.04 (±0.02) in young horses (up to 3 years of age) but 0.21 (±0.04) in older ones. These results suggest that a significant part of the inter-individual variation has a genetic origin. This paves the way to a genomic dissection of horse-nematode interactions which might provide predictive markers of susceptibility, allowing individualised drenching schemes.